ANALISIS EARNED VALUE TERHADAP BIAYA DAN WAKTU GEDUNG DIREKTORAT POLITEKNIK PU SEMARANG DENGAN PRIMAVERA P6 - Eka Nugraha, Noel; Sri Handayani, Fajar; Setiono, Setiono (Jurnal Riset Rekayasa Sipil, 2024)
Semarang PU Politeknik Building Construction Project is the construction of an educational building area developed in collaboration between PT Wika Gedung and PT Yodya Karya with a construction management consultant contract value of 3.9 billion and an executing contractor contract value of 281 billion. In this research, a research method with a quantitative descriptive approach was taken. This means that in this project, the condition of the project is described based on the analysis of the data obtained from the project. The data is then processed using descriptive and analytical methods. The Earned Value or EV concept method studies comparing the value of the work completed against the budget provided to carry out the work. The result of this research is to analyze using the Primavera P6 program whether the project is running at an appropriate cost and a schedule that does not deviate from the contract. The results of the analysis obtained for the implementation of the weekly analysis of the Earned Value indicator value obtained is positive which means that in the entire week of analysis, the project runs faster and more economically. The EAC and ETC values obtained are smaller than the contract cost, indicating that the project is planned to be completed at a smaller cost. The deviation value obtained is at an average of 0.08% with the smallest deviation being 0.0794% so the project will experience a profit of 8% on the completion date.